Formal caregivers’ knowledge, attitudes, and challenges in end-of-life care for people with advanced dementia: a qualitative study in Chinese nursing home - Ye Ouyang; Chunyu Cheng; Qing Sun; Linbing Chen; Liping Wang (BMC Nursing)
Abstract Background As frontline workers in caring for elderly people with dementia, the knowledge, attitudes, and working conditions of formal caregivers are crucial factors influencing the quality of end-of-life care. However, current studies focus on informal caregivers and lack of psychological discussion of formal caregivers. This study aims to investigate the knowledge and attitudes of formal carers implementing end of life care for patients with advanced dementia, along with the factors influencing their practice, to provide a foundation for enhancing the quality of end-of-life care for older adults. Methods A qualitative descriptive study utilizing semi-structured interviews. Twelve formal carers with experience in caring for individuals with advanced dementia were recruited from Dongguan City, Guangdong Province, China. Participants were selected using purposive sampling, incorporating the principle of maximum variation. Qualitative data were collected through face-to-face interviews and analyzed using thematic analysis, with NVivo14 software used for data organization. Results Various negative and positive aspects, along with specific needs, were identified. Four key themes emerged from the interview analysis: (a) Comprehensive knowledge and attitudes of formal caregivers towards end-of-life care for dementia, (b) perceived occupational challenges, (c) motivational factors facilitating care delivery, and (d) specific needs related to caregiving. Conclusion Formal carers of individuals with advanced dementia experience multiple pressures and challenges in their caregiving roles. Amid these difficulties, they develop self-coping strategies aligned with their role perceptions. Providing adequate care and support at all levels of the elderly end-of-life care system can alleviate caregiver stress and significantly enhance the overall quality of end of life care. Clinical trial number Not applicable.